Pengaruh Periklanan Media Elektronik dan Promosi Penjualan Terhadap Minat Dalam Transaksi Berulang Menggunakan Dompet Digital Dana - Ocsa Rabella Weles; Adil Fadillah; Pinto Jaya (Jurnal Informatika Kesatuan, 2021)
This study aims to determine whether Electronic Media Advertising and Sales Promotion have a partial and simultaneous effect on the Interest of Repetitive Transactions. The population in this study is the community who have used the application D A N A with a total sample of 110 people. The data analysis method uses multiple linear regression to determine the effect of Electronic Media Advertising, and Sales Promotion on the Interest of Repetitive Transactions. Data testing was performed using SPSS 20. The results of this study are as follows: (1) Electronic Media Advertising partially affects the Interest of Repetitive Transactions with the value of t arithmetic greater than t table (5,024> 1.65). (2) Sales promotion partially influences the Interest of Repetitive Transactions with t value greater than t table (3.478> 1.65). (3) Electronic Media Advertising and Sales Promotion partially have no effect on Repetitive Transaction Interest. (5) The two independent variables (Effect of Electronic Media Advertising and Sales Promotion) are able to explain variations in the dependent variable (Interest in Repeated Transactions) by 32.8%, while 67.2% Repurchase Interest is influenced by other independent variables. Keywords: Effect of Electronic Media Advertising, Sales Promotion and Repetitive Transaction Interest